Q-Switched and Mode-Locked Nd/Cr:YAG Ceramic Pulse Laser. (14th February 2020) - Saiki, T.; Hirota, N.; Kanemori, S.; Iida, Y.
Abstract : A mode-locked and Q-switched short pulse laser using the Nd 3+ /Cr 3+ :YAG ceramic has been constructed with a SESAM and Cr 4+ :YAG crystal optical switch based on excite state absorption (ESA). Laser oscillations of the pulse laser were observed experimentally. The Nd/Cr:YAG ceramic laser has a high conversion efficiency from white light (such as lamp light or solar light) to the laser. The Nd/Cr:YAG ceramic has a higher laser gain than the Nd:YAG laser for the same pumping power. The laser oscillation can be obtained very easily. A single-mode-locked laser pulse with fast modulation on the order of 100 ps was obtained in some pump power regimes when using the Cr 4+ :YAG crystal. The obtained pulse duration of the short pulse was a few hundred ps. A maximum peak power of 60 kW was obtained when using a SESAM. The same level of peak power (60 kW) was also obtained when using the Cr 4+ :YAG crystal.